World heritage and urban politics in Melaka, Malaysia : a cityscape below the winds - De Giosa, Pierpaolo (Asian heritages (Amsterdam, Netherlands), 2021)
This book presents a tale of heritage politics in the Malaysian historical city par excellence. Already celebrated as the first Malay sultanate and an important colonial trading port, Melaka has been on the UNESCO World Heritage List since 2008, on the strength of its multi-ethnic and multi-religious urban fabric. Yet, contrary to the expectations of heritage experts and aficionados, the global mission of safeguarding cultural heritage has become a tumultuous issue on the ground in Melaka. World Heritage and Urban Politics in Malaysia analyses how the World Heritage 'label' is being used by different actors- such as international organizations, nation states, and society at large- to generate new economic revenues and to attract investment for large-scale real estate development projects. In doing so, it reveals the complex and often contradictory stories behind heritage designations in urban milieus.